FRI0164 Differences between ra patients with and without ild from a united states tertiary referral center. (15th June 2017) - Meehan, R; Solomon, J; Crooks, J; Muram, D; Hoffman, E; Zelarney, P
Abstract : Objectives: To describe the characteristics of RA patients with and without ILD and to determine if medication use constitutes a risk factor for the development of ILD. Methods: The medical records of RA patients with and without ILD treated at one academic center between 2008 and 2016 were analyzed. Data extracted include: patient demographics, serology, medication use (prednisone, DMARDs, biologics or small molecule drugs), and self-reported disease activity as MDHAQ and RAPID 3 scores. The subtype of ILD was based upon HRCT imaging, and some patients through histology. Differences between RA-ILD patients and RA patients without ILD were determined by Fishers exact test, and t-tests with a p<0.05 were considered statistically significant. Results: The demographics and clinical data of 1, 024 RA non-ILD patients and 96 RA-ILD patients indicate ILD patients were older males, had a higher mortality and were less likely to have been never smokers (Table 1 ). At the onset of ILD diagnosis, 31% were on no medication, 56% on monotherapy (MTX 16%, prednisone 13%, Etanercept 7%, adalimumab or LEF 5%, Rituximab 4%, HCQ 3%, and <1% on infliximab, SSZ or tofacitinib) and 11% received combination therapy. Twenty five percent of the RA-ILD patients developed ILD preceding or coinciding with the diagnosis of RA. After the onset of ILD those patients were more likely to receive prednisone and less likely to receive MTX than those without ILD (p<0.05). The predominant types of ILD were as follows: UIP 27%, NSIP 15%, NSIP vs UIP 14%, and unclassifiable 9%. Conclusions: RA-ILD patients differed from RA patients without ILD in demographic characteristics, but not in self-reported measures of disease activity or serology. Thirty one percent of RA-ILD patients were not on any immunomodulatory medications at the time of ILD diagnosis, and 25% of RA-ILD patients developed ILD preceding, or coinciding with, the onset of active RA. Our results did not identify a specific drug class or biologic agent as a risk factor for developing ILD in RA patients. Disclosure of Interest: R. Meehan Grant/research support from: Eli Lilly and Company, J. Solomon: None declared, J. Crooks: None declared, D. Muram Employee of: Eli Lilly and Company, E. Hoffman: None declared, P. Zelarney: None declared